Effects of Climate Changes on Water Resources: A Case of Mindu Dam in Morogoro Municipality, Tanzania - Melchioly, Simon R (Tanzania Journal of Science, 2021)
This paper presents the findings of the research conducted in Morogoro Municipality, central Tanzania. The main objective of the research was to assess the climate change impacts on water resources, taking the Mindu Dam as the case study. The study methodology involved collection, processing and analysis of both primary and secondary data. Data collection involved acquisition of Dam water level data, climate data, and Landsat 8 satellite imagery. Research findings showed that the maximum air temperature increased at a rate of 0.045% on a span of 30 years, while rainfall has been decreasing with time. Also there has been a decreasing trend of water level in the Mindu Dam such that the coefficient of determination (R2) appeared to be very small (0.95%). The area also has witnessed an increasing trend in wind speed (R2 = 63.4%) for the period 2014 to 2019. The results showed coefficient of determination (R2) for water production/supply of only 1.58%, while for water demand the coefficient of determination was R2 = 77.13%. Findings on the changes in surface area covered by the Mindu Dam reservoir due to climate change impacts showed that for the period of 19 years, the Mindu Dam reservoir surface area decreased by 0.57%. Keywords: Climate change, water resources, Mindu Dam, land use change.